Sex-based differences in the association of resistance training levels with the risk of hypertension - Park, Jae Ho; Park, Hyun-Young (Frontiers in Public Health, 2024)
Introduction Hypertension is a primary risk factor for cardiovascular disease and all-cause mortality. This study investigated sex-based differences in the association between the risk of hypertension and resistance training (RT) levels, including training frequency and period. Methods We enrolled 162,102 participants from nationwide Korean cohorts. The training period (months) and frequency (per week) of RT were used to investigate the presence of an inverse dose–response relationship between RT levels and the risk of hypertension. Multiple logistic regression models were used to evaluate the risk of hypertension in relation to RT levels. Results The prevalence of hypertension in the study population was 36.28% in men and 26.94% in women. Performing RT was associated with an 8% reduction in the risk of hypertension in women but not in men. In women, performing RT for 3–4 days/week, compared with not performing RT, reduced the risk of hypertension by 11%, even after adjusting for covariates, including RT time per week and period. However, in men, no significant association was observed between training frequency and the risk of hypertension. We also evaluated the risk of hypertension by simultaneously considering both the RT frequency and period. Performing RT for 3–4 days/week and ≥5 days/week were markedly related to 14 and 11% hypertension risk reduction, respectively, in women who had been performing RT for at least 6 months. Conclusion Given that no inverse dose–response association was observed between RT frequency and hypertension risk, engaging in RT for 3–4 days/week for at least 6 months is recommended for women. Further longitudinal studies are needed to verify sex-based differences in the antihypertensive effects of regular RT.